The effect of abusive supervision variability on work–family conflict: The role of psychological detachment and optimism - Wang, Shuwei; Lin, Xiaoxin; Wu, Jun (Frontiers in Psychology, 2023)
Although a number of studies have examined the effects of abusive supervision variability, which refers to leaders engaging in differential abuse toward different subordinates within the team on work-related outcomes, scant research has investigated whether and how abusive supervision variability affects non-work outcomes. Drawing on the conservation of resources theory, the current study explores how abusive supervision variability affects work–family conflict through psychological detachment, as well as the moderating role of optimism. Results based on a survey of 260 employees from nine companies show that abusive supervision variability is significantly and positively related to work–family conflict. Psychological detachment mediates the effect of abusive supervision variability on work–family conflict. Optimism moderates the relationship between abusive supervision variability and psychological detachment and the indirect effects of abusive supervision variability on work–family conflict through psychological detachment. This study extends the literature on the effects of abusive supervision variability and provides several important practical implications.